COMBINED INHERITANCE OF GENES CONTROLLING MORPHOLOGICAL CHARACTERS AND RESTORATION OF POLLEN FERTILITY IN CASE OF CYTOPLASMIC MALE STERILITY IN FLAX (LINUM USITATISSIMUM L.) - E. A. Porokhovinova (Труды по прикладной ботанике, генетике и селекции)
As CMS sources 3 flax lines were used: gc-204 (open flower, sterile anthers), gc-208 and gc-188 are self fertile, their sterility occurs only in hybridization with other lines. The linkage group of rft3 (sterile tubular flowers) - pf1 (pink flower) - CSB1 (cilia on the bolls’ walls) with the frequency of crossing-over 10, 28 and 34cM, respectively was found. Independent inheritance of rft genes with others: YSED1(yellow seeds) and rft3-2; pbc1(light blue star-shaped flower) and rft3-6; rft3-7, rft5-2, rft6, rft7; ygp1 (yellow-green plant) and rft6, rft7; s1 and rft5-2, and independent inheritance of genes restoring pollen fertility of open flowers (RFO) with genes: RFO6, RFO8, RFO9 and pf-ad, RFO6, RFO7 and pbc1, RFO7 and s1 (white star-shaped flower, yellow seeds) were shown.